The Acquisition of Directionals in Two Mayan Languages - Pye, Clifton; Pfeiler, Barbara (Frontiers in Psychology, 2019)
We use the comparative method of language acquisition research in this article to investigate children’s expression of directional clitics in two Eastern Mayan languages – K’iche’ and Mam (Pye and Pfeiler, 2014; Pye, 2017). The comparative method in historical linguistics reconstructs the grammatical antecedents of modern languages and traces the evolution of each linguistic feature (Paul, 1889; Campbell, 1998). This history informs research on language acquisition by demonstrating how phonological and morphological features interact in the evolution of new uses for common inherited traits. Children acquiring modern languages must learn the arbitrary constraints imposed on their language by its history.